Association between Life’s Crucial 9 and psoriatic arthritis in U.S. adults: a cross-sectional study - Jiang, Jiefeng; Guan, Lyuxin; Gan, Ziqin; Wu, Zhili; Liang, Xiaofeng; Zhang, Zhiwen; Lyu, Yansi; Liang, Yunsheng (Frontiers in Medicine, 2025)
BackgroundPsoriatic arthritis (PsA) has been closely associated with an elevated risk of cardiovascular disease (CVD). Nevertheless, the connection between Life’s Crucial 9 (LC9), which serves as a holistic measure of cardiovascular health (CVH), and PsA remains insufficiently studied. This research aims to explore the potential relationship between LC9 and the prevalence of PsA.ObjectiveTo investigate the role of LC9 in PsA and explore its implications.MethodsThis study utilized a cross-sectional, population-based design, analyzing data from 7,531 U.S. participants aged 20 years or older, drawn from the 2005–2006 and 2009–2014 cycles of the National Health and Nutrition Examination Survey (NHANES). The LC9 score, which encompasses nine distinct components, was classified into three CVH categories: low, moderate, and high. To explore the association between LC9 scores and the prevalence of PsA, logistic regression models and restricted cubic splines were applied.ResultsIn the analyzed cohort of 7,531 individuals, participants with moderate or high CVH levels demonstrated a markedly reduced likelihood of developing PsA relative to those with low CVH. Additionally, a 10-point elevation in the LC9 score was associated with a 32% lower odds of having PsA. A notable interaction between LC9 and age was detected. Conversely, no meaningful link was found between LC9 and psoriasis without arthritis (PsC).ConclusionThe LC9 score and its subcomponents are significantly negatively correlated with the risk of PsA. This suggests that adherence to the lifestyle defined by LC9 is associated with a lower prevalence of PsA.